1983
DOI: 10.2307/1510441
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Problem Patterns among the Learning Disabled: Boys Aged 6–11

Abstract: Problem-behavior rating scale data on elementary-aged learning disabled and normal boys were factor analyzed according to the Quay and Peterson (Note 1) procedures. Somewhat different factors were identified for normal and learning disabled groups. The discussion focuses on the implications of the findings for a current issue in child psychopathology — hyperactivity as distinct from other conduct problems — and for classifying youngsters' behavior and emotional problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…In agreement with other studies that had examined psychosocial heterogeneity (e.g., Epstein, Bursuck, & Cullinan, 1985;Epstein, Cullinan, & Rosemier, 1983;Speece et al, 1985), Porter and Rourke concluded that children with LD are heterogeneous with regard to psychosocial functioning: There is no one pattern that is characteristic of all children with LD.…”
Section: Windsor Taxonomic Researchsupporting
confidence: 88%
“…In agreement with other studies that had examined psychosocial heterogeneity (e.g., Epstein, Bursuck, & Cullinan, 1985;Epstein, Cullinan, & Rosemier, 1983;Speece et al, 1985), Porter and Rourke concluded that children with LD are heterogeneous with regard to psychosocial functioning: There is no one pattern that is characteristic of all children with LD.…”
Section: Windsor Taxonomic Researchsupporting
confidence: 88%
“…Clearly, such a situation could easily lead to confounded and inconsistent results (Applebee, 1971;Torgesen & Dice, 1980). Differences in personality functioning among children with LD continue to be relatively neglected by the literature, although their existence has been well documented (Epstein, Cullinan, & Rosemier, 1983;Grieger 8c Richards, 1976;Paraskevopolous 8c McCarthy, 1970;Porter & Rourke, 1985). Different personality subtypes consistently have been reported in both the child psychopathology and LD literature (Achenbach & Edelbrock, 1978;Porter 8c Rourke, 1985), but the relationship between such diagnostic categories and attributional processes among children with LD has not been systematically addressed.…”
mentioning
confidence: 99%
“…A second subgroup of children with LD demonstrates symptoms of internalized socioemotional difficulties, such as anxiety, depression, and/or withdrawal (Grieger & Richards, 1976;McKinney & Speece, 1986;Paraskevopolous 8c McCarthy, 1970;Porter & Rourke, 1985). Others exhibit externalized symptoms, such as conduct problems, attentional difficulties, and antisocial tendencies (Epstein et al, 1983;Grieger & Richards, 1976;McKinney & Speece, 1986;Paraskevopolous 8c McCarthy, 1970;Porter 8c Rourke, 1985). A fourth subgroup has been found to experience concurrent internalizing and externalizing difficulties (Grieger 8c Richards, 1976;McKinney 8c Speece, 1986).…”
mentioning
confidence: 99%
“…Although the Epstein et al (1983) findings are informative with regard to younger boys, important questions remain about their applicability to older LD boys and to LD girls. Keogh, MajorKingsley, Omori-Gordon, and Reid (1982) acknowledged that the vast majority of LD research has focused on elementary-aged boys and that generalizations of findings to LD girls and adolescents must be considered tenuous at best.…”
mentioning
confidence: 99%